(untitled) (mathematica didactica, 2019)
In this paper, we describe how we used various historical multiplication algorithms in several classroom projects. On the one hand, we intended to initiate mathematically oriented reflection (in the sense of Skovsmose); on the other hand, we intended to make the pupils experience the historicity of mathematics. Our example shows that Jankvist’s categories “history as a tool” and “history as a goal” can occur simultaneously. From pupils’ products and recordings of classroom discussions, we draw conclusions about whether our goals were achieved and about how the material used could be further developed.